Unfractionated heparin in ruptured aortic aneurysms – narrative review - Tiago F. Ribeiro; Ricardo Correia; Rita Bento; Fábio Pais; Rita Soares Ferreira; Frederico Bastos Gonçalves; Carlos Amaral; Maria Emília Ferreira (Angiologia e Cirurgia Vascular, 2024)
INTRODUCTION: Portuguese estimates point out that nearly 20% of aortic aneurysms are treated in a ruptured setting, with in-hospital mortality reaching up to 50%. Although unfractionated heparin (UFH) is routine during elective surgery, this technical point is debatable when treating ruptured aneurysms. The authors aimed to review the literature on the topic of intraoperative heparinization with UFH within the intraoperative period of ruptured aortic aneurysms.